PROKES IN TALK SHOW AND ELECTRONIC CINEMA: REPRESENTATION OF SOCIAL GROUPS’ RESPONSES TO KPI REGULATION - Wahyudi, Agus Budi; Rahmatika, Laily (Universitas Muhammadiyah Semarang, 2021)
The Covid-19 pandemic has changed all lines of life, especially human hosts on talk shows and artists on electronic cinema are obliged to wear masks during the broadcast. The use of masks as an implementation of Prokes is accordance with KPI regulation to prevent the infection of Covid-19. The formulation of the research problem to describe how is the representation of social groups in responding to Deddy Corbuzier's post? The purpose of this research is to find the representation of social groups in responding to Deddy Corbuzier's post. The research design is in a qualitative with a descriptive approach. The research data are netizens expressions that come from Deddy Corbuzier's account. The data collection technique used was the observation and note-taking techniques. Data analysis uses critical discourse analysis and Representation with discursive constructs. The results show the representation of social groups that supported Deddy Corbuzier, as for the social groups: (1) verified accounts from the public figures (2) social groups of workers who presented complaints related to Prokes, and (3) unidentified groups represented variations such as KPI and electronic cinema. This offense is done by means of blasphemy, criticism, evaluation, and suggestions. The information representation of groups one and two are clear, while group three variegated cause conflict.